Baitul Maal Learning Organization, What Is the Role to Produce Quality Zakat Accounting Information? - Marjulin Marjulin; Yusri Hazmi; Hilmi Hilmi; Teuku Zulkarnain; Busra Busra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to provide a basic understanding of the importance of organizational learning in producing quality accounting information regarding zakat at Baitul Mal in Aceh. The purpose and objective of this study is to obtain findings and examine the impact of the model offered with the concept, the results of this study can be seen by how much impact organizational learning has in producing quality zakat accounting information. This study verifies whether the practice of organizational learning can produce quality accounting information. Verification is carried out by means of proof in the field. The method used in this research is descriptive method and explanatory research method, namely this research method wants to get a basic answer about the causes and effects of the factors causing the phenomenon raised in this study, data will be collected by distributing questionnaires to zakat managers who are members of the Baitul Mal institution. In Aceh, to obtain the results of this study, the data will be processed using a statistical tool, namely Partial Least Square (PLS) based on covariates. The results of this study prove that continuous organizational learning has an impact on the quality of the information produced, this can be seen from the hypothesis test showing that the organizational learning variable produces a number of 2.293 which is greater than the tcritical 1.65. Because the value of tarithmetic is greater than tcritical, then at an error rate of 5% it was decided to reject Ho. So based on the test results it can be concluded that organizational learning has a significant effect on the quality of zakat accounting information at the Baitul Mal in Aceh.